Big Data in Healthcare : Extracting Knowledge from Point-of-Care Machines - Amirian, Pouria; Lang, Trudie; van Loggerenberg, Francois (Springer International Publishing : Imprint: Springer, 2017)
This book reviews a number of issues including: Why data generated from POC machines are considered as Big Data. What are the challenges in storing, managing, extracting knowledge from data from POC devices? Why is it inefficient to use traditional data analysis with big data? What are the solutions for the mentioned issues and challenges? What type of analytics skills are required in health care? What big data technologies and tools can be used efficiently with data generated from POC devices? This book shows how it is feasible to store vast numbers of anonymous data and ask highly specific questions that can be performed in real-time to give precise and meaningful evidence to guide public health policy.
Keywords: Medicine.; Pharmaceutical technology.; Health informatics.; elektronické knihy; electronic books